The Role of Multistakeholders in Handling Stunting in Brebes District - Hanita, Arvida Rizzqie; Astuti, Retno Sunu; Warsono, Hardi (KnE Social Sciences, 2025)
Addressing stunting is agenda key priority in Brebes Regency. However, current efforts are largely dominated by government initiatives, with limited empowerment and involvement of other stakeholders. This study aims to analyze the roles of various actors and the obstacles they face in tackling stunting in Brebes Regency. Ratner’s Collaborative Governance Theory is used to identify challenges and opportunities for enhancing multi-actor collaboration. A descriptive qualitative approach was used, with data collected through observation and in-depth interviews. The findings reveal that effective stunting intervention in Brebes Regency requires broader actor participation, particularly from organizations that can serve as facilitators. Non-governmental organizations (NGOs), in particular, have the potential to contribute significantly due to their diverse human resources and extensive networks. This research recommends greater NGO involvement as part of a community-based social movement, enabling them to act as a bridge between the community and the government in addressing stunting in Brebes Regency.